The Relationship Between Empathy and Forgiveness in Adolescent Who Have a Cheating Parent - Kamila Sagafia; Henny Regina Salve (Publikasi Indonesia, 2022)
This study aims to determine the relationship between empathy and forgiveness in adolescents whose parents have an affair. This study uses quantitative research methods. The sampling technique used in this research is snowball sampling. The sample in this study consisted of 55 adolescents. The measurement of forgiveness data was carried out using a modified forgiveness scale from McCullough, Root, & Cohen (1999). Measurement of empathy was carried out using a modified empathy scale from Davis (1983). The data analysis technique used is Pearson Product Moment correlation analysis technique. Based on the results of the analysis, it is known that there is a very significant positive relationship between empathy and forgiveness in adolescents whose parents have an affair with a significance value of 0.002 (p<0.01). These results indicate that the hypothesis that there is a relationship between empathy and forgiveness in adolescents who have cheating parents is acceptable. Furthermore, the relationship has a positive direction, that is, the higher the level of empathy, the higher the level of forgiveness (forgiveness). Conversely, the lower the level of empathy, the lower the forgiveness.